Family communication and genetics: Developing a framework for effective interventions - Wiens, Miriam E (University of Ottawa (Canada), 2008)
Objective. To create a theory-based framework to guide the development of interventions for assisting genetics health services clients to communicate results of genetic testing to at-risk family members. Methods. Systematic review methods were used to collect evidence on the barriers and facilitators of disclosure. After appraisal of several theories against key criteria, the Theory of Planned Behaviour (TPB) was chosen as the theory to base the framework on. The framework was developed through a qualitative process which incorporated the all the available evidence from the literature. A preliminary examination of the utility of the framework was done through a cross-sectional survey. Results. The framework explains the act of disclosing a genetic test results to at-risk family members in terms of the TPB. Results from the cross-sectional survey, conducted in a population not previously studied, were generally consistent with the information presented in the framework and found in the literature. Conclusions. The framework has potential to be used in developing interventions; however, results need to be replicated in prospective studies with larger samples.
Keywords: Speech Communication.; Health Sciences, Medicine and Surgery.